2017
DOI: 10.1111/echo.13569
|View full text |Cite
|
Sign up to set email alerts
|

The additional utility of two‐dimensional strain in detection of coronary artery disease presence and localization in patients undergoing dobutamine stress echocardiogram

Abstract: Two-dimensional strain at peak stress had an incremental value over DSE visual assessment/ wall-motion score index (WMSI) in reducing false-positive results of DSE. Two-dimensional strain at peak stress had greater accuracy than DSE alone not only in detection of significant CAD but also in detection of number of vessels with significant lesion as well as CAD localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
6
12
0
Order By: Relevance
“…In our study, 76.1% subjects had significant CAD which cor- fer between these groups. 7,8,13 Median GLS also varied significantly among subjects without significant CAD and subjects with SVD, DVD, or TVD in our study. It is similar to the results found with mean GLS in the study by Moustafa et al 10…”
Section: Baseline Characteristicssupporting
confidence: 58%
See 4 more Smart Citations
“…In our study, 76.1% subjects had significant CAD which cor- fer between these groups. 7,8,13 Median GLS also varied significantly among subjects without significant CAD and subjects with SVD, DVD, or TVD in our study. It is similar to the results found with mean GLS in the study by Moustafa et al 10…”
Section: Baseline Characteristicssupporting
confidence: 58%
“…Roushdy et al reported a moderate agreement with GLS at peak stress (κ = 0.499, P < .001). 8 The agreement between territorial strain and CAG in detecting LAD disease was substantial while it was moderate for LCX disease and fair for RCA lesions. The finding with 2D-strain at peak stress in the study by Roushdy et al was similar with good agreement in LAD territory (κ = 0.775, P<.001) but fair agreement in LCX territory (κ = 0.263, P<.01) and moderate agreement in RCA territory (κ = 0.415, P < .001).…”
Section: Agreement Of Dse and Strain Imaging With Cagmentioning
confidence: 91%
See 3 more Smart Citations